A Trajectory of Decoloniality from “De” to “Re” in Fahmida Riaz’s Poem “Come Let Us Create A New Lexicon” - Iqbal, Aniqa; Yaqoob, Munazza (Journal of Research in Humanities, 2025)
This research explores the trajectory of decolonial praxis in Fahmida Riaz’s poem “Come Let Us Create A New Lexicon,” using theoretical key concepts from decolonial theorists such as Walter Mignolo, Aníbal Quijano, and Gloria Anzaldúa. The study traces the progress of this trajectory from “epistemic disobedience” to “epistemic reconstruction” as articulated by Mignolo and Quijano. The research positions this journey within the state of “nepantla” as described by Anzaldúa. Together, these terms facilitate the process of de-essentializing and rethinking colonial epistemologies, leading to a “pluriversal” and multi-perspective worldview. This framework is situated in Riaz’s poetry to analyse how the engagement with these decolonial ideas illustrates the dismantling of colonial/dominant epistemic structures and the reconstruction of diverse narratives through repressed knowledge systems within Pakistani society. Riaz’s poem endeavours to liberate ignored narratives to be incorporated in the central epistemes to build a heterogeneous community. The findings of this study contribute to a nuanced understanding of Pakistani literature and its engagement with decolonial praxis, which becomes a tool for social liberation through epistemic reconstruction.